Integrated School Branding Strategies for Rebuilding Public Trust: A Case Study of an Islamic Private Junior High School in Indonesia - Febri Susilowati; Achadi Budi Santosa; Bambang Sudarsono (CV. Media Digital Publikasi Indonesia, 2026)
Public trust is a critical determinant of the sustainability and competitiveness of private schools in an increasingly competitive educational environment. This study aims to analyze the integrated school branding strategies implemented by SMPIT Istiqamah Balikpapan to rebuild public trust following a decline in student enrollment. A qualitative case study design was employed to obtain an in-depth understanding of the branding practices adopted by the school. Data were collected through semi-structured interviews with 15 purposively selected participants, including the principal, foundation representatives, the Student Admission Committee (SPMB) coordinator, vice principals, teachers, administrative staff, and a school committee representative. The interview data were complemented by observations and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and verification. The findings reveal five interrelated branding strategies that contributed to rebuilding public trust: (1) strengthening school identity through the alignment of vision, graduate competency standards, and school culture; (2) expanding strategic partnerships with government agencies, community organizations, industries, and international institutions; (3) developing achievement-based branding by systematically promoting academic and non-academic excellence; (4) strengthening student admission services (SPMB) through scholarship programs, service excellence, and responsive communication; and (5) implementing integrated promotional communication that combines digital branding, experiential marketing, and positive word-of-mouth. These strategies collectively enhanced institutional reputation, strengthened stakeholder engagement, and contributed to increased student enrollment. This study proposes an integrated school branding perspective, emphasizing that sustainable public trust is built through the interaction of institutional identity, educational quality, stakeholder relationships, service excellence, and strategic communication rather than through promotional activities alone. The findings provide practical implications for school leaders and policymakers seeking to strengthen the competitiveness and long-term sustainability of private educational institutions.